Monitoring M-Protein, Therapeutic Antibodies, and Polyclonal Antibodies in a Multiparametric Mass Spectrometry Assay Provides Insight into Therapy Response Kinetics in Patients with Multiple Myeloma - Charissa Wijnands; Peter G. A. Karel; Jolein Gloerich; Gad Armony; Anastasia Tzasta; Corrie M. de Kat Angelino; Luciano Di Stefano; Vincent Bonifay; Theo M. Luider; Martijn M. VanDuijn; Sandra J. Croockewit; Elizabeth A. de Kort; et al. (Pharmaceutics)
Background/Objectives: Multiple Myeloma (MM) is a hematologic malignancy caused by clonally expanded plasma cells that produce a monoclonal immunoglobulin (M-protein), a personalized biomarker. Recently, we developed an ultra-sensitive mass spectrometry method to quantify minimal residual disease (MS-MRD) by targeting unique M-protein peptides. Therapeutic antibodies (t-Abs), key in MM treatment, often lead to deep and long-lasting responses. However, t-Abs can significantly decrease the total polyclonal immunoglobulin (Ig) levels which require supplemental IgG infusion. Here, we demonstrate the simultaneous monitoring of M-proteins, t-Abs, and polyclonal Ig-titers using an untargeted mass spectrometry assay, offering a comprehensive view of therapy response. Methods: Sera collected between 2013 and 2024 from four patients and cerebrospinal fluid (CSF) from one patient who received various t-Abs were analyzed with MS-MRD. M-protein sequences were obtained with a multi-enzyme de novo protein sequencing approach. Unique peptides for M-proteins and t-Abs were selected based on linearity, sensitivity, and slope coefficient in serial dilutions. Ig constant regions were monitored using isotype-specific peptides. Results: The MS-MRD multiplex analysis provided detailed information on drug concentrations and therapy response kinetics. For example, in two patients with refractory disease over five lines of therapy, the MS-MRD analysis showed that the deepest responses were achieved with bispecific t-Ab (teclistamab) treatment. M-protein and t-Ab were also detectable in the CSF of one patient with MS-MRD. Conclusions: This proof-of-concept study shows that the multiplex monitoring of the M-protein, any t-Ab combination, and all Ig-isotypes within one mass spectrometry run is feasible and provides unique insight into therapy response kinetics.